A Study of medical errors - Abdoljabbari, Morteza (Archives of Advances in Biosciences, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Any time Throughout the human story, when man has been exposed to boredom and health problems , he has used the expertise of those in the life of medicine and treatment. The holy Prophet (PBUH) has been narrated as saying, "The experts are healers of people, and in case the healers are themselves ill, who will treat the patients? From the Holy narration by the Holy Prophet (PBUH), we learn that the important figures in the society, especially the physicians, have to be always in good health both physically and morally. The medical team being known as outstanding characters, are highly valuable in the society. In the past they were known as 'healers', a title which is used to call the God showing that Islam pays a special attention to the physicians. It is so incredible to utilize this value in guiding the people, especially the patients in the best way possible. . It has to be noted that those with the highest quality features, characters, and self-efficient personalities shall be better benefited. . The health of the healers is therefore, an undeniable necessity. Studies have revealed that even a 24-hour monthly work shift may triple the occurrence of medical errors. As the most serious part of the present study is the definition of the term "Fault" in medicine, it becomes mandatory to define it morphologically and terminologically to see what it really refers.